Associations between multimodal fitness assessments and rowing ergometer performance in collegiate female athletes - Holmes, C. J.; Hornikel, B.; Sullivan, K.; Fedewa, M. V. (Sports, 2020)
The purpose was to examine the association of critical power from a three-minute all-out row (CP3-min) and peak power from a one-stroke maximum test (1-Stroke) with laboratory-based fitness assessments (peak oxygen consumption [V.O2peak] and Wingate anaerobic test [WAnT]) and 6000 m (6K) and 2000 m (2K) rowing ergometer performance. Thirty-one female collegiate rowers (20.2 ± 1.1 years, 70.9 ± 6.9 kg, and 172.2 ± 4.8 cm) participated in fitness and rowing performance testing. Pearson`s correlations, linear regression, and Cohen`s q were used to determine statistical relationships. Absolute VO2peak values displayed significant correlations with 6Ktotal (-0.68), 6Ksplit (-0.68), 2Ktotal (-0.64), and 2Ksplit (-0.43). Relative VO2peak displayed significant correlations with 6Ktotal (-0.36), and 6Ksplit (-0.37). CP3-min demonstrated significant correlations with 6Ktotal (-0.62), 6Ksplit (-0.62), 2Ktotal (-0.61), and 2Ksplit (-0.99). For 2Ksplit, a significant difference was observed between relative VO2peak and CP3-min correlations with a "large" effect size (q = 2.367). Furthermore, 1-Stroke showed significant associations with 6Ktotal (-0.63), 6Ksplit (-0.63), 2Ktotal (-0.62), and 2Ksplit (-0.44), while WAnT produced non-significant correlations. Absolute VO2peak CP3-min accounted for significant proportions of variance observed with performance measures (p < 0.05). Practitioners should consider incorporating CP3-min and 1-Stroke as additional tests for gauging rowing performance.